Two new species of Tillandsia (Bromeliaceae) from Mexico - Espejo, Adolfo; López-Ferrari, Ana Rosa; Till, Walter (Instituto de Ecología, A.C., 2008)
Tillandsia grossispicata from Colima, Jalisco, Guanajuato, and Michoacán and T. inopinata from Hidalgo, Guanajuato, Querétaro, San Luis Potosí and Tamaulipas are described and illustrated. The new species are compared with T. fasciculata Sw., a taxon with similar characteristics. A comparative table and a distribution map of the new taxa are included.